2008
DOI: 10.1038/sj.bjc.6604321
|View full text |Cite
|
Sign up to set email alerts
|

The role of early life genistein exposures in modifying breast cancer risk

Abstract: Review of the existing literature suggests that consumption of soy foods or an exposure to a soy isoflavone genistein during childhood and adolescence in women, and before puberty onset in animals, reduces later mammary cancer risk. In animal studies, an exposure that is limited to the fetal period or adult life does not appear to have the same protective effect. A meta-analysis of human studies indicates a modest reduction in pre-and postmenopausal risk when dietary intakes are assessed during adult life. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 51 publications
(74 reference statements)
8
101
0
3
Order By: Relevance
“…Environmental chemicals with estrogenic activity (xenoestrogens, such as BPA, and the pesticide, dieldrin) and other EDCs not exhibiting estrogenic behavior (such as dioxin and atrazine) may cause abnormal mammary gland development (Markey et al 2001, Munoz-de-Toro et al 2005, Fenton 2006, Enoch et al 2007, Vandenberg et al 2007 or may increase the risk of breast cancer (Durando et al 2007, Cameron & Foster 2009). A number of epidemiological studies have suggested that the dietary intake of phytoestrogens decreases the risk of breast cancer in humans (Badger et al 2005, Warri et al 2008, Wu et al 2008. Soy consumption during childhood and adolescence has been consistently linked to a marked reduction in breast cancer risk in Asian and AmericanAsians (Korde et al 2009), in agreement with some experimental studies showing that pubertal exposure to genistein (G), a natural phytoestrogen that is prevalent in plants (Wang et al 2006), reduces mammary cancer risk in rodent models (Warri et al 2008).…”
Section: Introductionsupporting
confidence: 53%
“…Environmental chemicals with estrogenic activity (xenoestrogens, such as BPA, and the pesticide, dieldrin) and other EDCs not exhibiting estrogenic behavior (such as dioxin and atrazine) may cause abnormal mammary gland development (Markey et al 2001, Munoz-de-Toro et al 2005, Fenton 2006, Enoch et al 2007, Vandenberg et al 2007 or may increase the risk of breast cancer (Durando et al 2007, Cameron & Foster 2009). A number of epidemiological studies have suggested that the dietary intake of phytoestrogens decreases the risk of breast cancer in humans (Badger et al 2005, Warri et al 2008, Wu et al 2008. Soy consumption during childhood and adolescence has been consistently linked to a marked reduction in breast cancer risk in Asian and AmericanAsians (Korde et al 2009), in agreement with some experimental studies showing that pubertal exposure to genistein (G), a natural phytoestrogen that is prevalent in plants (Wang et al 2006), reduces mammary cancer risk in rodent models (Warri et al 2008).…”
Section: Introductionsupporting
confidence: 53%
“…Human epidemiological data and in vitro animal studies suggest that genistein may possess breast cancer preventive properties (review by Warri et al, 2008) by altering expression of BRACA1 and PTEN and perhaps by epigenetic mechanisms. Similarly, in vitro data support an effect on mammary tumorogenesis, as exposure of human mammary cells to genistein altered the expression of certain cancer-related genes (Moon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding management of gilts during the early phase of mammary cell accretion (from 90 days of age until puberty; Sorensen et al, 2002) has an impact on mammary development (Farmer et al, 2004;Sorensen et al, 2006), and it is likely that specific feed ingredients may be useful in stimulating this process of mammogenesis. Phytoestrogens have gained increasing interest in recent years because of their potential health benefits in prevention of mammary cancer (review by Warri et al, 2008) and other benefits such as alleviation of bone loss in postmenopausal women -E-mail:Chantal.Farmer@agr.gc.ca (review by Lister et al, 2007). These naturally occurring plant compounds with estrogenic or anti-estrogenic activities (depending on the concentration of endogenous estrogens present; Sun Hwang et al, 2006) comprise three major classes.…”
Section: Introductionmentioning
confidence: 99%
“…They have gained much interest in recent years because of their potential health benefits in prevention of mammary cancer (review by Warri et al, 2008) and alleviation of bone loss in post-menopausal women (review by Lister et al, 2007). Phytoestrogens comprise three major classes, namely, isoflavones (including genistein), lignans and coumestans.…”
Section: Introductionmentioning
confidence: 99%